The Role of Islamic Spiritual Guidance in Overcoming Loneliness in the Elderly: Study at the Mandalika Social Service Center for the Elderly (PPSLU) - Saimun, Saimun; Hanafi, Hanafi; Haryani, Septi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The Mandalika Elderly Social Service Center shows that the elderly often experience death due to the loss of close family members and lack of social attention. This study aims to describe the level of equality experienced by the elderly and analyze the role of Islamic Spiritual Guidance in overcoming loneliness. With a qualitative descriptive approach and case study, this study involved three elderly aged 70-80 years who regularly follow spiritual guidance programs. Data were obtained through in-depth interviews and analyzed using data reduction, validation, and triangulation techniques. This study is expected to provide deeper insight into the psychosocial conditions of the elderly and the importance of spiritual support. The results showed that inequality has a significant impact on the mental well-being of the elderly, especially due to loss and lack of social attention. Islamic Spiritual Guidance has proven to be an effective solution in building emotional resilience, providing emotional support, and reducing loneliness. Through religious activities, the elderly find peace of mind, strengthen social relationships between congregations, and improve their psychosocial well-being. Thus, spiritual guidance not only helps overcome loneliness but also contributes to improving the overall quality of life of the elderly.